Functional Outcomes of Early Rehabilitation Following Proximal Femur Fracture Fixation in Elderly Patients: A Prospective Comparative Study. - Agrawal, Nilesh Kumar; Roshan, Reetesh; Kumar, Raman; Kumar, Santosh; Khan, Farhan Ahmed (Student’s Journal of Health Research Africa, 2026)
Background: Proximal femur fractures in elderly patients are associated with impaired mobility, poor functional outcomes, and prolonged hospitalization. Early postoperative rehabilitation may enhance recovery and improve clinical outcomes. Objective: To compare functional outcomes, mobility, and hospital stay between early and conventional rehabilitation following proximal femur fracture fixation in elderly patients. Methods: This prospective comparative study included 60 elderly patients (≥60 years) undergoing surgical fixation of proximal femur fractures at IGIMS, Patna. Patients were allocated to early rehabilitation (within 48 hours; n=30) or conventional rehabilitation (postoperative day 5; n=30). Functional outcome was assessed using the Harris Hip Score (HHS), mobility by the Timed Up and Go (TUG) test, and duration of hospital stay. Follow-up was conducted up to 12 months. Results: The early rehabilitation group demonstrated significantly better HHS scores (80.27±8.0 vs. 71.35±9.1), shorter TUG times (14.96±3.0 vs. 18.32±4.1 seconds), and reduced hospital stay (6.85±1.5 vs. 9.67±2.0 days) compared with the conventional rehabilitation group (all p<0.001). Conclusion: Early rehabilitation following proximal femur fracture fixation significantly improves functional recovery, mobility, and reduces hospital stay in elderly patients. Recommendation: Early postoperative rehabilitation should be incorporated into standard care protocols for elderly patients undergoing proximal femur fracture fixation.